Topical Pimecrolimus as a New Optional Treatment in Cutaneous Sarcoidosis of Lichenoid Type - Antonella Tammaro; Claudia Abruzzese; Alessandra Narcisi; Giorgia Cortesi; Francesca Romana Parisella; Pier Paolo Di Russo; Gabriella De Marco; Severino Persechino (Case Reports in Dermatological Medicine)
We report the case of cutaneous sarcoidosis of lichenoid type successfully treated with pimecrolimus. For the first time in the literature, we propose the use of this topical calcineurin inhibitor for the treatment of the cases refractory to common therapy regimens.